2018
DOI: 10.1093/jas/sky439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microbial phytase on mucin synthesis, gastric protein hydrolysis, and degradation of phytate along the gastrointestinal tract of growing pigs1

Abstract: An experiment was conducted to test the hypothesis that pigs fed diets supplemented with exogenous phytase reduce mucin synthesis in the small intestine, increase protein hydrolysis in the stomach, increase breakdown of phytate along the gastrointestinal tract, and increase mineral and AA digestibility. A diet based on corn, soybean meal, and canola meal was formulated to meet requirements for growing pigs except for Ca and P, which were lower than requirements. Three additional diets were formulated by adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
10
11
2
Order By: Relevance
“…Colonic P secretion is supported by data reported by Larsen and Sandstrom (42) who demonstrated a higher ileal compared with faecal apparent P digestibility in cannulated pigs. Our findings conflicted with Mesina et al (38) and Rosenfelder-Kuon et al (35) who demonstrated a similar ileal and faecal apparent P digestibility. Nonetheless, none of these studies including the present can exclude secretion and reabsorption of P in the caecum and colon.…”
Section: Calcium and Phosphorus Absorption Along The Gastrointestinal...contrasting
confidence: 99%
“…Colonic P secretion is supported by data reported by Larsen and Sandstrom (42) who demonstrated a higher ileal compared with faecal apparent P digestibility in cannulated pigs. Our findings conflicted with Mesina et al (38) and Rosenfelder-Kuon et al (35) who demonstrated a similar ileal and faecal apparent P digestibility. Nonetheless, none of these studies including the present can exclude secretion and reabsorption of P in the caecum and colon.…”
Section: Calcium and Phosphorus Absorption Along The Gastrointestinal...contrasting
confidence: 99%
“…A recent study [ 113 ] determined that pigs fed a corn–soybean-meal-based diet with up to 3000 FTU exogenous E.coli -derived 6-phytase/kg feed (Experiment 1) or a corn–soybean meal or a corn–soybean meal-rapeseed cake diet supplemented with 1500 FTU/kg feed (Experiment 2), had greater concentrations of Ins(1,2,5,6)P 4 and lower concentrations of inositol phosphate 5 ( InsP 5 ) isomers (Ins(1,2,3,4,5)P 5 ; Ins(1,2,4,5,6)P 5 ) in ileal digesta (Experiment 1) for diets supplemented with microbial phytase (1500 and 3000 FTU/kg feed). The Ins(1,2,5,6)P 4 was considered the limiting isomer of InsP degradation for the used microbial phytase, in agreement with previous studies [ 116 , 117 ]. Thus, to increase the digestibility of dietary plant P, strategies to degrade InsP 6 to lower forms of InsP are warranted because lower InsP forms can almost be completely digested by pigs [ 113 ].…”
Section: Utilization Of Selected Minerals In Pigssupporting
confidence: 86%
“…It should be noted that there are strong kosmotropic influences of anionic phosphoryl groups in phytate, which stabilize protein structures by affecting the aqueous medium around the molecule [ 7 , 22 ]. The total secretion of mucin in the intestine increases by interacting with phytase [ 12 , 23 , 24 ], resulting in an increased loss of endogenous amino acids due to the low digestibility of mucin structural proteins. Another effect of phytate on protein digestibility in the intestinal lumen is associated with the phytase interaction that increases sodium ion (Na + ) influx into the intestine.…”
Section: Discussionmentioning
confidence: 99%